Cord blood Streptococcus pneumoniae‐specific cellular immune responses predict early pneumococcal carriage in high‐risk infants in Papua New Guinea. (18th December 2016) - Francis, J. P.; Richmond, P. C.; Strickland, D.; Prescott, S. L.; Pomat, W. S.; Michael, A.; Nadal‐Sims, M. A.; Edwards‐Devitt, C. J.; Holt, P. G.; Lehmann, D.; van den Biggelaar, A. H. J.
Summary: In areas where Streptococcus pneumoniae is highly endemic, infants experience very early pneumococcal colonization of the upper respiratory tract, with carriage often persisting into adulthood. We aimed to explore whether newborns in high‐risk areas have pre‐existing pneumococcal‐specific cellular immune responses that may affect early pneumococcal acquisition. Cord blood mononuclear cells (CBMC) of 84 Papua New Guinean (PNG; high endemic) and 33 Australian (AUS; low endemic) newborns were stimulated in vitro with detoxified pneumolysin (dPly) or pneumococcal surface protein A (PspA; families 1 and 2) and compared for cytokine responses. Within the PNG cohort, associations between CBMC dPly and PspA‐induced responses and pneumococcal colonization within the first month of life were studied. Significantly higher PspA‐specific interferon (IFN)‐γ, tumour necrosis factor (TNF)‐α, interleukin (IL)‐5, IL‐6, IL‐10 and IL‐13 responses, and lower dPly‐IL‐6 responses were produced in CBMC cultures of PNG compared to AUS newborns. Higher CBMC PspA‐IL‐5 and PspA‐IL‐13 responses correlated with a higher proportion of cord CD4 T cells, and higher dPly‐IL‐6 responses with a higher frequency of cord antigen‐presenting cells. In the PNG cohort, higher PspA‐specific IL‐5 and IL‐6 CBMC responses were associated independently and significantly with increased risk of earlier pneumococcal colonization, while a significant protective effect was found for higher PspA‐IL‐10 CBMC responses. Pneumococcus‐specific cellular immune responses differ between children born in pneumococcal high versus low endemic settings, which may contribute to the higher risk of infants in high endemic settings for early pneumococcal colonization, and hence disease. Abstract : In settings highly endemic area for Streptococcus pneumoniae infections, infants may display activated cellular immune responses to the pneumococcal protein PspA at birth that independent of maternal‐derived antibodies contribute to the risk of early pneumococcal colonization.